The efficiency of silencing expression of the gene coding STAT3 transcriptional factor and susceptibility of bladder cancer cells to apoptosis - Bednarek, Ilona (Termedia Publishing House, 2012)
AIM OF THE STUDY: Abnormalities in signaling as well as altered gene expression have been identified in numerous diseases, including cancer. The biological functions of signal transducer and activator of transcription 3 (STAT3) are very broad. It is thought that STAT3 can also contribute to oncogenesis. RNA interference (RNAi) is one of the most efficient tools for silencing gene expression within cells. The main goal of the study was to verify the effectiveness of STAT3 gene silencing and its influence on cell proliferation and activation of apoptosis in bladder cancer cells. MATERIAL AND METHODS: The study was conducted on cellular material, which was the stable human bladder cancer cell line T24. The synthesis of shRNA (short hairpin RNA) interfering with the STAT3 gene was based on pSUPER. neo expression vector. The gene expression at the mRNA level was determined by the real-time PCR method. The influence of STAT3 gene silencing on apoptosis induced in cells with modulated STAT3 expression was evaluated using parallel quantification of mono- and oligonucleosomal DNA degradation of genomic DNA. RESULTS: In transfected T24 cells, the STAT3 mRNA expression decreased to the level of 68.3% compared to the scrambled (SCR) control. Silencing the STAT3 gene induced changes in the phenotype of T24 cells. Statistically significant differences in cell proliferation (p = 0.0318) and apoptosis induction (p = 0.0376) were observed. CONCLUSIONS: Application of the designed shRNA for the STAT3 gene contributed to a decrease of expression of the examined gene. It also decreased the proliferation and increased the susceptibility to apoptosis in T24 bladder cancer cells.